Онтологічні аспекти розвитку інноваційних форм бізнесу в національній економіці - Гончаренко, Оксана Володимирівна; Honcharenko, Oksana; Земляна, Анастасія Віталіївна; Zemliana, Anastasia (Дніпровський державний технічний університет, 2021)
Обґрунтовано імперативи глобальних трансформацій світового господарства та специфічні особливості національної економіки в контексті становлення інноваційних форм бізнесу й активізації інноваційного процесу. Визначені еволюційні детермінанти цифрової трансформації суспільного господарства та аргументовано напрями модернізаційних перетворень економіки України. Констатовано галузеві особливості національної економіки в контексті модернізаційних змін і реалізації глобальних трендів; акцентовано на важливості дослідження інституціональних чинників економічної динаміки та регулюючих впливах інституціонального механізму в реалізації інноваційного розвитку. Встановлено, що сучасні зміни глобальної економіки й цифрові трансформації національних господарств відбуваються з різними темпами в галузевому і секторальному сегментах, але базуються на об’єктивних процесах поглиблення й розподілу праці, поширення інтеграції і інновацій. Акцентовано, що поширенню інноваційних форм бізнесу в національній економіці не сприяють сформовані інституціональні та еволюційні обмеження. The imperatives of global transformations of the world economy and the specific features of the national economy in the context of the formation of innovative forms of business and activation of the innovation process are substantiated; The evolutionary determinants of the digital transformation of the social economy are determined and the directions of modernization transformations of the economy of Ukraine are argued; The sectoral features of the national economy in the context of modernization changes and implementation of global trends are stated; The importance of the study of institutional factors of economic dynamics and regulatory influences of the institutional mechanism in the implementation of innovation development is focused. It has been established that modern changes in the global economy and digital transformations of national farms take place at different pace in sectoral and sectoral segments, but are based on objective processes of deepening and distribution of labor, distribution of integration and innovation. New forms of labor organization, which are mainly based on network ties and interactions, contributed to the spread of services and its innovation segment, which turned out to increase volumes of operations under outsourcing, outstafing, freelance. The rapid growth of IT outsourcing is stated, in particular in the field of cloud computing, bots development of chatting bots, blockchain technology, use of artificial intelligence and automated training. It is accented that the dissemination of innovative forms of business in the national economy do not contribute to the formed institutional and evolutionary restrictions. Specific evolutionary restrictions for innovative changes in the national economy began a scale of technological lag of key industries and economics as a whole, the influence of the shadow economy and formed institutional "traps" in key areas, crisis economic, social, political factors. Institutional problems are due to the inefficiency of basic institutions, which are formed by the basis for economic interactions (market, economy, competition) and the lack of effective instruments and forms of budgetary tax and monetary regulation. Theoretical and methodological provisions deepen the practical principles of institutional regulation and ensuring the innovative development of the national economy and innovative forms of business organization.
Ontological aspects of development innovative forms of bisiness in the national economy
Keywords: глобальні тенденції; global trends; модернізація; modernization; цифровізація; digitalization; інноваційний розвиток; innovation development; інноваційний бізнес; innovative business; інституціональне забезпечення; institutional support; послуги; services